STRENGTHENING SHARIA ECONOMIC LITERACY THROUGH HALAL TRANSACTION EDUCATION TO THE COMMUNITY OF TELUK BAKUNG VILLAGE, TANJUNG PURA DISTRICT - Muhammad Sadri; Kahar Mashuri; Dina Alviany (International Journal of Economic, Technology and Social Sciences (Injects), 2026)
Sharia economic literacy is an important factor in shaping people's economic behavior in accordance with Islamic sharia principles. However, there are still many rural communities who do not understand the concept of halal transactions comprehensively so that daily economic practices are still dominated by habits without paying attention to the aspects of contracts, transparency, and justice. This research aims to analyze the strengthening of sharia economic literacy through halal transaction education to the people of Teluk Bakung Village, Tanjung Pura District. The study used a qualitative method with Norman Fairclough's Critical Discourse Analysis (CDA) approach. Data was obtained through observation, in-depth interviews, Focus Group Discussions (FGD), and documentation, then analyzed through three dimensions of CDA, namely text analysis, discursive practices, and social practices. The results of the study show that halal transaction education is able to increase public understanding of the concept of sharia economics, the principle of contracts, the prohibition of usury, gharar, and maysir, as well as encourage changes in attitudes in applying the values of honesty, openness, and responsibility to economic activities. Education also forms a collective awareness that halal transactions are part of the implementation of Islamic teachings as well as an instrument for community economic empowerment. This study concludes that halal transaction education is an effective strategy in strengthening sharia economic literacy and supporting the realization of village economic development that is fair, sustainable, and based on sharia values.